2006
DOI: 10.1111/j.1540-5915.2006.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxes of Online Investing: Testing the Influence of Technology on User Expectancies*

Abstract: At an increasing rate, individual investors are taking personal control over their financial destinies by investing their money online. Compared to offline do-it-yourself approaches, evidence suggests that investors exhibit lofty expectations and perform significantly worse after going online. However, little is understood about the mechanisms fueling expectancies, the role technologies play in their formation, or how technologies shape investment decisions. Therefore, this article explores the paradoxical nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 90 publications
(228 reference statements)
2
65
0
Order By: Relevance
“…In the following we unpack these explanations. Looney et al (2006) distinguish between activities that involve different skills, each confined to a discrete domain, and activities that employ a blend of skills from two or more domains. In their study of online financial trading they viewed computer self-efficacy and investment self-efficacy as two distinct components, but combined online trading self-efficacy and perceived efficacy at making the investment decisions into single construct that consisted of items in the form of: "I can use an online investment web-site to choose investments wisely".…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the following we unpack these explanations. Looney et al (2006) distinguish between activities that involve different skills, each confined to a discrete domain, and activities that employ a blend of skills from two or more domains. In their study of online financial trading they viewed computer self-efficacy and investment self-efficacy as two distinct components, but combined online trading self-efficacy and perceived efficacy at making the investment decisions into single construct that consisted of items in the form of: "I can use an online investment web-site to choose investments wisely".…”
Section: Discussionmentioning
confidence: 99%
“…Another study described a three-level model of self-efficacy in the area of online investment (Looney et al, 2006). The model defines the relations among the perceived efficacy in the technical component of the task, Computer Self-Efficacy in this case, efficacy at the functional domain component, Investment Self-Efficacy, and their combination, i.e., Online Investment Self-Efficacy.…”
Section: Measuring Self-efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, research on computer self-efficacy (Marakas, Yi, & Johnson, 1998) can inform researchers in regards to how computing confidence can affect benefits outcomes. For instance, research has found that computer selfefficacy was positively related to user expectations about the outcomes of online self-service investing (Looney, Valacich, Todd, & Morris, 2006). Research has also found that employees with high levels of Volume 9 Issue 1 technology anxiety were less satisfied with ESS and less likely to use ESS than those with lower levels of technology anxiety (Meuter, Ostrom, Bitner & Roundtree, 2003).…”
Section: E-benefitsmentioning
confidence: 99%